Educational Scout: Pramuka Sebagai Wadah Pendidikan Karakter Bangsa - Subandi, Endi; Asbari, Masduki; Anggraeni, Vira (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to find out that teachers are the most important component in improving the quality of education. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from Jerri Muhammad's YouTube channel entitled Mandatory Scouts, 2022 Independent Curriculum, Minister of Education and Culture Regulation No. 63 of 2014 from Nadiem Anwar Makarim's perspective. The results of this study explain the importance of Scouting as a mandatory extracurricular in schools in the context of the Independent Curriculum. They stated that during the Covid-19 pandemic, Scout activities in schools had stopped, however, the Minister of Education and Culture and Research and Technology, Anwar Makarim, emphasized that Scouts supported character education and the Independent Curriculum.